Complete monotonicity, completely monotonic degree, integral representations, and an inequality related to the exponential, trigamma, and modified Bessel functions - Qi, Feng; Wang, Shu-Hong (Global Journal of Mathematical Analysis, 2014)
In the paper, the authors verify the complete monotonicity of the difference e^1/t-ψ'(t) on (0,∞), compute the completely monotonic degree and establish integral representations of the remainder of the Laurent series expansion of e^1/z, and derive an inequality which gives a lower bound for the first order modified Bessel function of the first kind. These results show us some new properties and relations of the exponential, trigamma, the first kind modified Bessel functions and the hypergeometric series.Keywords: property; connection; completely monotonic function; completely monotonic degree; integral representation; difference;exponential function; trigamma function; hypergeometric series; inequality; modified Bessel function.